Research of the Workspace Property and Kinematics Analysis of a Kind of Industrial Robot - Fan Yu; Cai Ganwei (Jixie chuandong)
A kind of parallel series robot is designed,the characteristic are as following: shoulder and elbow joints are transferred out by parallelogram linkages and driven by ballscrew,which makes it own larger rigidity and better dynamic performance. It keeps the good characteristics of larger workspace series robot. The kinematics analysis of this robot is carried out,the workspace is solved by means of an improved way of printing points,and then,the boundary analysis method is proposed to calculate the workspace. The results show that the computation of the boundary analysis method is smaller and the result is clear. The volume and performance index are calculated based on the solved workspace. And it proves that this kind of robot has better workspace property.